2009
DOI: 10.1002/jso.21421
|View full text |Cite
|
Sign up to set email alerts
|

Extensive lymphadenectomy in colorectal cancer with isolated para‐aortic lymph node metastasis below the level of renal vessels

Abstract: The findings of this study suggest that PALN dissection increases the survival of patients with isolated PALN metastasis from CRC, and that it has a tolerable morbidity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
119
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 18 publications
7
119
0
1
Order By: Relevance
“…It is also well known that patients with isolated PALN metastasis were found to be very rare in the range 1.0-1.3% [15,16] , and a majority of PALN metastasis accompanied other distant sites of metastasis, such as the liver, lung, extraabdominal LNs, or peritoneal dissemination. Therefore, systemic chemotherapy was generally indicated for patients with PALN metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also well known that patients with isolated PALN metastasis were found to be very rare in the range 1.0-1.3% [15,16] , and a majority of PALN metastasis accompanied other distant sites of metastasis, such as the liver, lung, extraabdominal LNs, or peritoneal dissemination. Therefore, systemic chemotherapy was generally indicated for patients with PALN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Min et al [15] evaluated the outcome of 38 patients with metachronous-isolated PALN metastasis and reported that the median OS in the PALND group (n = 6) was 34 months, which was significantly better than 14 months in the non-resected group (n = 34; p = 0.034). Choi et al [16] reported the outcome of 77 patients after PALND for metachronous-isolated PALN metastasis. Five-year OS and the median OS in the PALND group (n = 24) were 53.5% and 64 months, which were significantly better compared with the non-resected group (n = 53) (12% and 33 months, respectively) [16] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in rectal cancer, clinical significance of extended lymph node dissection in the paraaortic region has not been well addressed. To the best of our knowledge, few clinical studies have been performed on the outcome of extensive lymphadenectomy in colorectal cancer (CRC) with isolated PAN metastasis [13]. To date, no study was designed to assess the efficacy of paraaortic lymphadenectomy in rectal cancer.…”
Section: Introductionmentioning
confidence: 99%